TRANSFORMATION OF JAPANESE CULTURE FOR INCREASING JAPANESE COMMUNICATIVE COMPETENCE - Herniwati, Herniwati; Aneros, Noviyanti (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
This study aims to assess the preparation of the design model of learning, teaching materials conversational skills for intermediate level, which focuses on the transformation of Japanese culture as innovation and efforts to improve speaking skills in learning Chukyu Kaiwa. This research uses the Research and Development (R D) and experiment. The result shows asignificant increase in students’ Japanese speaking skills and their understanding of Japanese culture. The transformation of Japanese culture is able to attract the students to compare and find similarities with Indonesian culture.